Impact of geography and travel distance on outcomes in epithelial ovarian cancer: a national cancer database analysis. Issue 2 (19th November 2020) - Daruvala, Ava; Lucas, F Lee; Sammon, Jesse; Darus, Christopher; Bradford, Leslie
Abstract : Background: As ovarian cancer treatment shifts to provide more complex aspects of care at high-volume centers, almost a quarter of patients, many of whom reside in rural counties, will not have access to those centers or receive guideline-based care. Objective: To explore the association between proximity of residential zip code to a high-volume cancer center with mortality and survival for patients with ovarian cancer. Methods: The National Cancer Database was queried for cases of newly diagnosed ovarian cancer between January 2004 and December 2015. Our predictor of interest was distance traveled for treatment. Our primary outcomes were 30-day mortality, 90-day mortality, and overall survival. The effect of treatment on survival was analyzed with the Kaplan-Meier method. Multiple logistic regression for binary outcomes and Cox proportional hazards regression for overall survival were used to assess the effect of distance on outcome, controlling for potential confounding variables. Results: A total of 115 540 patients were included. There was no statistically significant difference in 30- or 90-day mortality among any of the travel distance categories. A statistically significant decrease in 30-day re-admission was found among patients who lived further away from the treating facility. A total of 105 529 patients were available for survival analysis, and survival curves significantly differed between distance strata (p<0.0001). The adjusted regression models demonstrated increased long-term mortality in patients who lived farther away from the treating facility after controlling for potential confounding. Conclusion: Although 30- and 90-day mortality do not differ by travel distance, worse survival is observed among women living >50 miles from a high-volume treatment facility. With a national policy shift toward centralization of complex care, a better understanding of the impact of distance on survival in patients with ovarian cancer is crucial. Our findings inform the practice of healthcare delivery, especially in rural settings.